(untitled) (Bangladesh Journal of Medical Science, 2017)
Background: Dyslipidemia is linked to the risk for coronary ischemic and cardiovascular disease. Considering the absence of national reference level for lipids in Bangladesh the present study was undertaken to look into the pattern of lipid levels among patients seeking laboratory services in a private medical college hospital. Materials and Methods: This cross sectional study was carried out in Ibn Sina Medical College Hospital in Dhaka city. Patients with antilipid and other medication which might affect the outcome were excluded. Consenting and eligible subjects seeking laboratory services were included in the study. Total 970 subjects finally entered in the study. Total cholesterol [TC], triglyceride and HDL-cholesterol [HDL-c] were measured by enzymatic colorimetric method. LDL-cholesterol [LDL-c] was derived using Friedewald equation. Data were expressed mean±SD, number (percent) as appropriate. Statistical analyses were carried out using SPSS version 17 tool. A p value <0.05 was taken as level of significance. Results: Male female ratio of the total subjects was 53.9:46.1. Of the total participants 27.1% were between 41-50 age group and 71% were between 31-60 years. Mean (SD) triglyceride, total cholesterol, HDL-c and LDL-c level for all participants was 182±134, 194±44, 38.4±11.5 and 119±37 respectively. Mean value of HDL-c for all subjects was 38.4mg/dl where as its cutoff value is 40 mg/dl and 50 mg/dl for male and female respectively suggesting relatively large number of subjects had HDL-c dyslipidemia of the study subjects. Percent subjects with isolated abnormal lipid component were 51%, 41%, 73.2% and 33.3% for triglyceride, total cholesterol, HDL-c and LDL-c respectively. Of the total subjects 22% had abnormal level of lipid for all four components. Conclusions: The data showed pattern of lipid levels of the subjects seeking laboratory services of a tertiary care hospital which might be taken a trend in the Bangladeshi population. Dyslipidemia appeared to be relatively high among the subjects studied of which HDL-c dyslipidemia was more prominent. Bangladesh Journal of Medical Science Vol.16(3) 2017 p.375-379